2002
DOI: 10.1080/00984100290071063
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of Bisphenol a on the Polecat ( Mustela Putorius )

Abstract: Bisphenol A (BPA), an environmental estrogen derived from the plastic industry, was given orally via incorporation into the food of 30 male and female polecats at 3 different doses (10, 50, or 250 mg/kg body weight/day) for 2 wk with 10 animals acting as controls. Several hormone levels in the plasma were determined as well as the activities of the phase I and II biotransformation enzymes 7-ethoxyresorufin O-deethylase (EROD), cytosolic glutathione S-transferase (GST), and UDP-glucuronosyltransferase (UDPGT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In addition to binding and activating the TR (Moriyama et al 2002), BPA has been shown to induce UDP-GT activity in European polecats (Nieminen et al 2002). Since UDP-GT regulates the rate-limiting step in T 4 metabolism in rats and presumably in humans, induction of this enzyme could underlie the reduction in T 4 observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to binding and activating the TR (Moriyama et al 2002), BPA has been shown to induce UDP-GT activity in European polecats (Nieminen et al 2002). Since UDP-GT regulates the rate-limiting step in T 4 metabolism in rats and presumably in humans, induction of this enzyme could underlie the reduction in T 4 observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Zoeller et al (2005) and Xu et al (2007) found effects at the lowest doses administered (1 mg/kg body weight and 0.1 mg/L drinking water, respectively). Studies conducted in nonpregnant animals generally found no effect of BPA on thyroid hormone levels (Nieminen et al 2002; Seidlova-Wuttke et al 2005). …”
mentioning
confidence: 98%
“…In vitro and rodent studies report inconsistent effects (Nieminen et al, 2002a; Nieminen et al, 2002b; Xu et al, 2007; Zoeller et al, 2005) and epidemiological studies, which have predominately been cross-sectional, have also been equivocal. Two studies from China reported that occupational exposure to BPA exposure was associated with elevated FT 3 and FT 4 and reduced TSH concentrations (Wang et al, 2012; Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nieminen et al (2002a), support not indicated, examined the effects of bisphenol A [purity not indicated] exposure on hormone levels in the European polecat (Mustela putorius). There were no significant effects on plasma levels of testosterone, estradiol, FSH, or thyroid hormones.…”
Section: Utility (Adequacy) For Cerhr Evaluation Processmentioning
confidence: 99%
“…4.2.1.3 Other mammals: Nieminen et al (2002a), support not indicated, examined the effects of bisphenol A exposure on hormone levels in the European polecat (Mustela putorius). Five animals/group/sex [age not reported] were administered bisphenol A [purity not reported] in feed at concentrations providing doses of 0, 10, 50, or 250 mg/kg bw/day for 2 weeks.…”
Section: Experimental Animalmentioning
confidence: 99%